`(2x^3 - x^2 + x + 5)/(x^2 + 3x + 2)` Write the partial fraction decomposition of the improper rational expression.

Expert Answers

An illustration of the letter 'A' in a speech bubbles

`(2x^3-x^2+x+5)/(x^2+3x+2)`

Since the rational expression is an improper rational expression, so we have to express it as sum of simpler fractions with degree of polynomial in the numerator less than the degree of polynomial in the denominator.

Dividing using long division yields,

`(2x^3-x^2+x+5)/(x^2+3x+2)=2x-7+(18x+19)/(x^2+3x+2)`

Since the polynomial don not completely, so we have to continue with the partial fractions of the remainder expression,

Let's factorize the denominator of the remainder expression,

`x^2+3x+2=x^2+x+2x+2`

`=x(x+1)+2(x+1)`

`=(x+1)(x+2)`

Let`(18x+19)/(x^2+3x+2)=A/(x+1)+B/(x+2)`

`=(A(x+2)+B(x+1))/((x+1)(x+2))`

`=(Ax+2A+Bx+B)/((x+1)(x+2))`

`=(x(A+B)+2A+B)/((x+1)(x+2))`

`:.(18x+19)=x(A+B)+2A+B`

Equating the coefficients of the like terms,

`A+B=18`   --------- equation 1

`2A+B=19`  -------- equation 2

Now solve the above equations to get the solutions of A and B,

Subtract equation 1 from equation 2

`2A-A=19-18`

`A=1`

plug the value of A in equation 1,

`1+B=18`

`B=18-1`

`B=17`

`(18x+19)/(x^2+3x+2)=1/(x+1)+17/(x+2)`

`:.(2x^3-x^2+x+5)/(x^2+3x+2)=2x-7+1/(x+1)+17/(x+2)`

 

Approved by eNotes Editorial Team
An illustration of the letter 'A' in a speech bubbles

You need to decompose the fraction in simple irreducible fractions, such that:

`(2x^3 - x^2 + x + 5)/(x^2 + 3x + 2) = (2x^3 - x^2 + x + 5)/((x+1)(x+2))`

`(2x^3 - x^2 + x + 5)/(x^2 + 3x + 2) = A/(x+1) + B/(x+2) `

You need to bring to the same denominator all fractions, such that:

`2x^3 - x^2 + x + 5 = A(x+2) +B(x+1) `

You need to group the terms having the same power of x:

`2x^3 - x^2 + x + 5 = x(A+B) + 2A+B`

Comparing the expressions both sides yields:

`A+B = 1 => B = 1-A`

`2A+B=5 => 2A + 1 - A = 5 => A = 4 => B = -3`

Hence, the partial fraction decomposition of the improper rational expression is `(2x^3-x^2+x+5)/((x+1)(x+2)) = 4/(x+1) - 3/(x+2)`

 

%MCEPASTEBIN%

Posted on

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial